Non Surgical Management of Large Periapical Lesions Using Calcium Hydroxide - A Report of Two Cases - Ballal, Nidambur Vasudev; Jain, Isha (The Journal of Dentists, 2016)
Nonsurgical management of periapical lesions has shown to have a high success rate. In the present case series, two large periapical lesions were treated with conservative therapy by the use of calcium hydroxide as an interim root canal dressing. The lesions resulted in successful resolution and healed completely. Long term follow-up of these cases is required to assess the success rate achievable by this mode of treatment.